EKSPLORASI PRAKTIK PEMBELAJARAN BAHASA INDONESIA MENGGUNAKAN LKPD: STUDI KUALITATIF TENTANG HAMBATAN DAN KEBUTUHAN INOVASI DI KELAS V DI SD N 39 KOTA LUBUKLINGGAU - Elce Purwandari; Winda Gustiana; Heru Prasetyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to explore the practice of using Student Worksheets (LKPD) in Indonesian language instruction for fifth-grade students at SD Negeri 39 Lubuklinggau. The main problem addressed in this research is the low level of students’ critical thinking skills, which appears to be associated with the suboptimal use of LKPD both in terms of its design and classroom implementation. Teachers tend to rely on lecture-based methods and conventional worksheets that focus only on practice questions, without encouraging idea exploration or collaborative discussion. This research employed a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with classroom teachers, the principal, and students, as well as documentation. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation. The findings reveal that while teachers do make and use LKPD, the materials are not yet fully innovative or tailored to the students’ characteristics. The worksheets are often visually unappealing and do not sufficiently foster critical thinking. Students respond enthusiastically when the LKPD is designed in an engaging and interactive manner, though they still require support to develop independent learning habits. Teachers and schools express a need for training and resources to effectively develop LKPD based on active learning models such as inquiry-based learning.